PERSEPSI MASYARAKAT TENTANG REVITALISASI SURAU LAKUAK SEBAGAI LEMBAGA DAKWAH ISLAM DI JORONG BATANG PAMO NAGARI PIANGGU KECAMATAN IX KOTO SUNGAI LASI KABUPATEN SOLOK - Hani Fatun Khasanah; Refika Mastanora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main issue in this research is that children have packed daily schedules, ranging from full-day school to Quranic recitation at the surau (Islamic prayer house). The perception of children, as expressed by their parents, regarding the lack of playtime as an important part of child development is a serious concern. Therefore, in-depth research is needed on how the community views the revitalization of Surau Lakuak as an Islamic da'wah institution that can support children's development in spiritual and social aspects. The purpose of this discussion is to determine the community's perception of the revitalization of Surau Lakuak as an Islamic da'wah institution and the supporting and inhibiting factors in the revitalization of Surau Lakuak. The type of research used by the author is descriptive qualitative research, to obtain data from the problems studied. The data collection techniques used were observation of activities at Surau Lakuak, interviews with the surrounding community, pioneers, teachers, jorong (hamlet) leaders, and Surau Lakuak congregation, as well as documentation of activities at Surau Lakuak. This research shows that the revitalization of Surau Lakuak has had a positive impact on the religious and social life of the community, with the community having a positive perception of the increasingly active role of the surau in religious activities and religious education. The discussion reveals that the main supporting factors are community participation and contributions from overseas residents, although there are challenges such as limited road access and a shortage of teaching staff. In conclusion, the revitalization of Surau Lakuak can continue to develop with ongoing support, providing significant benefits to the community in increasing spiritual awareness and strengthening social solidarity.